Energy-aware communications 17th international workshop, EUNICE 2011, Dresden, Germany, September 5-7, 2011. proceedings - EUNICE (Conference) 2011 Dresden, Germany); Lehnert, Ralf.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 17th EUNICE 2011 Workshop on energy-aware communications, held in Dresden, in September 2011. The proceedings comprise 16 full papers and 7 poster papers which are presented together with the abstracts of the 3 invited talks. The topics covered are: network architectures; ad-hoc and wireless networks; system simulation; network planning, optimization, and migration; traffic engineering; quality of experience; and energy efficient architectures.
Electronic reproduction.
Keywords: Computer networks -- Congresses; Telecommunication systems -- Environmental aspects -- Congresses; Electronic books